Primary umbilical endometriosis presenting with umbilical bleeding: A case report - Ifeoma Ogamba; Samuel Napolitano; Linus Chuang; Deborah August; Kathleen LaVorgna (Case Reports in Women's Health, 2022)
Endometriosis is a condition in which endometrial tissue implants outside the uterine cavity, which can cause cyclic pain, dysmenorrhea, dyspareunia, and infertility. Endometriosis implants are typically seen on pelvic peritoneal surfaces and extra-pelvic disease is uncommon. We present an interesting case of primary umbilical endometriosis in a patient who presented with umbilical bleeding with a history of pelvic inflammatory disease complicated by bilateral tubo-ovarian abscesses. She was found to have an umbilical mass, which was resected, and the pathology was consistent with endometriosis. The objective of this case report is to detail the case and discuss diagnosis and management of umbilical endometriosis. It is important to recognize that umbilical endometriosis can occur in patients with no surgical history.